2012
DOI: 10.1152/ajprenal.00507.2011
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of long-term oral nicotine in a rat model of spontaneous proteinuria

Abstract: Many proteinuric renal conditions are accompanied by renal inflammation. Nicotine is known to have anti-inflammatory properties and is used in oral form to help subjects quit smoking. A potential anti-inflammatory role of nicotine in proteinuric renal diseases has not been investigated to date. We therefore evaluated the effects of oral nicotine in a rat model of proteinuria-induced renal inflammation. We used a well-established model of adult (24 wk of age) male Munich-Wistar-Frömter rats. Animals were given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…In support of this hypothesis, COX-2 inhibition in vivo has been shown to reduce the pro-angiogenic and pro-atherosclerotic effects of nicotine[35]. Although the administration of nicotine resulted in worse kidney injury in the anti-Thy1 model of acute nephritis, in the Munich-Wistar-Frömter rat, a model of proteinuria-induced renal inflammation, the long-term administration of nicotine (20 to 100 μg/mL in the drinking water) resulted in improvements in proteinuria and renal function[72]. The plasma levels of cotinine varied from 139 ng/ml for the lower dose of nicotine to more than 500 ng/mL for the higher doses of nicotine.…”
Section: Biologic Effects Of Nicotinementioning
confidence: 99%
“…In support of this hypothesis, COX-2 inhibition in vivo has been shown to reduce the pro-angiogenic and pro-atherosclerotic effects of nicotine[35]. Although the administration of nicotine resulted in worse kidney injury in the anti-Thy1 model of acute nephritis, in the Munich-Wistar-Frömter rat, a model of proteinuria-induced renal inflammation, the long-term administration of nicotine (20 to 100 μg/mL in the drinking water) resulted in improvements in proteinuria and renal function[72]. The plasma levels of cotinine varied from 139 ng/ml for the lower dose of nicotine to more than 500 ng/mL for the higher doses of nicotine.…”
Section: Biologic Effects Of Nicotinementioning
confidence: 99%
“…The density of renal macrophages and myofibroblasts were reduced by nicotine and the level of renal inflammatory markers was also reduced. The authors suggested evaluating nicotine as a potential therapeutic option for treating proteinuric kidney disease [12]. A further study was performed to investigate the effect of nicotine in an experimental mouse model of injury to the skin and subsequent healing during the inflammatory phase of repair.…”
Section: Introductionmentioning
confidence: 99%
“…Lower plasma cotinine levels may result in different effects and signals. In contrast to the adverse events of chronic nicotine, several studies reported anti-inflammatory effects of nicotinic acetylcholine receptor agonists in ulcerative colitis, sepsis, hypersensitivity pneumonitis, experimental type 1 diabetes and even in renal ischaemic-reperfusion injury [23][24][25]. In an experimental mouse model of lipopolysaccharide (LPS)-induced septic AKI, administration of nicotinic agonists significantly abrogated renal leucocyte infiltration and attenuated kidney injury.…”
mentioning
confidence: 99%
“…Long-term oral nicotine administration showed a preserved kidney function, a reduced proteinuria, a reduced renal inflammation and protected progression of renal structural damage in Munich Wistar Frömter rats with proteinuria. However, these renoprotective effects may be limited to the specific animal models in which they are described [23].…”
mentioning
confidence: 99%